2004
DOI: 10.1002/mds.20128
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mutations in the epsilon‐sarcoglycan gene in patients with different subtypes of primary dystonias

Abstract: Primary dystonias represent a clinically and genetically heterogeneous group of movement disorders. Mutations in the epsilon-sarcoglycan (SGCE) gene have been found recently to cause myoclonus-dystonia (MD). Considerable clinical variation of SGCE mutation carriers leads to the hypothesis that mutations in the SGCE gene might also be relevant for other subtypes of dystonias. To determine the contribution of mutations in the SGCE gene in patients with different subtypes of dystonias, we analyzed the coding sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Similar studies could be performed in human. Rescreen of the homologous exon in patient DNA samples, where SGCE mutations have been reported to be uncommon in phenotypic myoclonus‐dystonia patients [32–36], might yield new SGCE mutations that are associated with this exon. Future research directed at understanding the roles these mRNA variants play in the brain could contribute to the understanding of the pathogenesis of DYT11 dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies could be performed in human. Rescreen of the homologous exon in patient DNA samples, where SGCE mutations have been reported to be uncommon in phenotypic myoclonus‐dystonia patients [32–36], might yield new SGCE mutations that are associated with this exon. Future research directed at understanding the roles these mRNA variants play in the brain could contribute to the understanding of the pathogenesis of DYT11 dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…In most neurology subspecialty practices, the vast majority of patients with dystonia are adults with primary focal or segmental disease. Genetic factors likely play a major role in late-onset primary dystonia since 8–27% of patients with primary late-onset dystonia have one or more family members affected with dystonia [ 5 - 9 ] and several of the primary dystonias inherited in Mendelian fashion (DYT1, DYT5, DYT6, DYT11, and DYT12) begin focally, show incomplete penetrance and exhibit variable anatomical expressivity [ 10 - 12 ]. These facts suggest that sporadic late-onset dystonia, much like Parkinson's disease, is a complex disorder with contributions from multiple genes and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, screening efforts have shown that DYT1 and DYT11 mutations are only rarely associated with adult-onset sporadic dystonia. [10][11][12] In contrast to DYT1 and DYT11, DYT6 dystonia commonly affects muscles of the head, neck, and larynx, with relatively less limb involvement. 13,14 Moreover, in comparison with DYT1, DYT6 dystonia seems to exhibit a later age-of-onset and often remains focal or segmental in distribution.…”
mentioning
confidence: 99%